PENGARUH GAYA KEPEMIMPINAN DEMOKRATIS TERHADAP KINERJA KARYAWAN (STUDI PADA PT. TIMOR EXPRESS INTERMEDIA KUPANG) - Tri Santi Octavia Olla; Struce Andriyani (Universitas Nusa Cendana, 2017)
The purpose of this research is to know how the Democratic Leadership Style influence onEmployee Performance. To analyze the data analysis technique was used Descriptive Statistics,Inferential Analysis and Hypothesis Testing.The results showed that the Democratic LeadershipStyle applied to the PT. Timor Express Intermedia Kupang consists of four (4) indicators ofDelegation of Responsibility, Activeness, Decision-Making, and The Empathy that have a positiveinfluence on Employee Performance. This is evidenced by tcount > ttable that is equal to 7,433>2.012896, so the hypothesis is accepted and Employee Performance (Y) can be explained by theDemocratic Leadership Style (X) amounted to 54.6% while the remaining 45.4% is explained byother factors. The company needs to maintain and implement Democratic Leadership Style so thatthe performance of employees will be increased and when the performance of employeesincreased, the organization's goals will be achieved.Keywords : Democratic Leadership, Employee Performance